Study of Groundwater Gradient Distribution in Akeguraci Village, Oba Tengah District, Tidore Islands City, North Maluku Province - Meidhy Ardiansyah; Abdul Kadir D. Arif (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Tidore Islands is an area with a high population growth rate, making clean water essential for the lives of the people of Akeguraci Village. Therefore, this study aims to determine the distribution of groundwater potential in Akeguraci Village. The data was then processed using Microsoft Excel software to generate groundwater depth data. Groundwater depth data was obtained by subtracting the water surface depth from the basin height. This subtraction yielded the groundwater depth. Groundwater elevation data was obtained by subtracting the topographic elevation data from the groundwater depth. The Excel data was then entered into the software application to create a groundwater distribution map to determine the flow and distribution of groundwater levels in Akeguraci Village. The groundwater distribution pattern resulting from the groundwater gradient map at the internship location in Akeguraci Village shows that groundwater distribution is spread westward or towards the coast.